Web-Based Inventory Information System Design of Research and Community Service - Alamksyah, Arif S Nur; Muis, Mappalotteng Abdul; Fathahillah, Fathahillah (Journal of Research and Innovation, 2023)
This study aims to produce a website-based inventory information system that is appropriate for user needs and to become a supporting tool for the Institute for Research and Community Service (LP2M) in a practical inventory data collection process. The research method used in this research is Research and Development using the Prototype development model with the stages of Requirements analysis, Prototype Design Making, Prototype Evaluation, System Coding, System Evaluation and System Use. This research was conducted through a trial phase, the first stage was to test the validity of the instrument, the results of the validity test from two experts were 97.5% with a very valid category. The results showed that the Web-Based Goods Inventory information system for the Institute for Research and Community Service (LP2M) Makassar State University was valid and feasible to use after being tested using the ISO 25010 standard. In the test results obtained: a) functionality suitability is worth 100% which means that all functions of the system are running well; b) reliability was carried out using the WAPT 10.1 tool in testing successful sessions, successful pages, successful hits, a success percentage of 99.62% were categorized as 'good'; c) usability with the number of respondents 7 obtaining an average percentage of effectiveness of 95% which is categorized as very good; d) performance efficiency with success presentation at point A or very good; and e) portability by accessing the system on a mobile device or in several web browsers on a desktop and can run properly.Keywords: Inventory Information System, ISO/IEC 25010, Web, Prototype